2022
DOI: 10.1038/s41598-022-05930-4
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the acoustic activity of beaked whales and sperm whales recorded during a naval training exercise off eastern Canada

Abstract: Experimental research has shown that beaked whales exhibit strong avoidance reactions to naval active sonars used during antisubmarine warfare training exercises, including cessation of echolocation and foraging activity. Behavioural responses to sonar have also been linked to strandings and mortality. Much of the research on the responses of beaked whales and other cetaceans to naval active sonar has occurred on or near U.S. naval training ranges, and the impacts of sonar in other regions remain poorly unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Sub-lethal effects are similarly challenging to observe, but experimental research has demonstrated that exposure to sonar can significantly disrupt normal behaviours in beaked whales, leading to altered dive cycles, the cessation of foraging activity over sustained periods, and long-range displacements from an affected area [ 56 , 59 , 69 , 70 ]. This scale of disturbance is likely to incur energetic costs and may result in a loss of foraging opportunities, underscoring the need for careful consideration of sonar use in marine environments [ 69 , 71 ].…”
Section: Threatsmentioning
confidence: 99%
“…Sub-lethal effects are similarly challenging to observe, but experimental research has demonstrated that exposure to sonar can significantly disrupt normal behaviours in beaked whales, leading to altered dive cycles, the cessation of foraging activity over sustained periods, and long-range displacements from an affected area [ 56 , 59 , 69 , 70 ]. This scale of disturbance is likely to incur energetic costs and may result in a loss of foraging opportunities, underscoring the need for careful consideration of sonar use in marine environments [ 69 , 71 ].…”
Section: Threatsmentioning
confidence: 99%
“…One way to overcome some of these limitations is by using Passive Acoustic Monitoring (PAM), which consists of deployment of underwater recorders to capture sounds from the surrounding environment. PAM is a cost-effective, non-invasive method that is widely used for long-term studies to assess and monitor marine biodiversity, including species distribution and behavior of acoustically active species 9 , 11 , 24 . PAM also allows year-round data collection independent of sea or weather conditions in remote areas, like the High Arctic.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple mass strandings of beaked whales have been associated with high-intensity anthropogenic sound sources, including naval sonar (Bernaldo de Quir os et al, 2019;D'Amico et al, 2009;Simonis et al, 2020). These acute events have motivated research into whether and how beaked whales respond to different types and intensities of anthropogenic noise (e.g., Aguilar de Soto et al, 2006;Cholewiak et al, 2017;Stanistreet et al, 2022;Tyack et al, 2011). Anthropogenic sound can disrupt the foraging dive cycles of beaked whales (Falcone et al, 2017), potentially leading to cumulative sublethal impacts resulting from reduced foraging opportunities (New et al, 2013;Pirotta et al, 2018), or to symptoms similar to decompression sickness that can lead to injury or death (Hooker et al, 2009(Hooker et al, , 2012.…”
Section: Introductionmentioning
confidence: 99%